ANALISIS DAMPAK PENGGUNAAN MEDIA SOSIAL TIKTOK PADA PERILAKU MORAL ANAK KELAS V SEKOLAH DASAR - Wafiq Rifqi Fatmawati; Wawan Shokib Rondli; F. Shoufika Hilyana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The use of social media TikTok can cause addiction which can affect children's moral behavior. Due to the existence of video content that is less educational. This study aims to analyze the impact of social media use TikTok and the moral behavior of fifth grade students at SDN Sumberjo. Moral behavior is behavior that is in accordance with the rules and values ​​in the society where the individual lives. The research method used is a qualitative method with a case study approach. This research will be conducted in class V SDN Sumberjo, Ngawen Blora. Collecting data in this study is observation, interviews, and documentation. Validity test using source triangulation. Data analysis techniques using data reduction, data presentation, and conclusions. The results of this study conclude that TikTok social media has a positive impact, namely as a means for entertainment media, encouragement to make creative videos so that they are famous, can add to relationships and also have negative impacts such as losing track of time and speaking more impolite or impolite words. have courtesy to elders. With social media, TikTok greatly influences the moral behavior of fifth graders at SDN Sumberjo. Many children follow the trendy style on social media TikTok, such as imitating the pargoy sway, imitating impolite words with the names of animals. This of course requires supervision in its use, so that the character and manners in the child are maintained and moral.